Sosialisasi abdominal stretching sebagai upaya menurunkan nyeri dismenorea pada remaja putri - Fibrila, Firda; Herlina, Herlina; Ridwan, M. (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Problems surrounding menstruation, especially menstrual pain, are often discussed by women, especially young women. Menstrual pain or known as dysmenorrhea can occur in some women caused by hormonal, uterine contractions and inflammation. In adolescents, dysmenorrhea that occurs is more due to unstable hormones and causes discomfort. One of the non-pharmacological efforts to overcome this condition is by doing abdominal stretching. The socialization carried out in this service activity aims to increase the understanding and mastery of adolescents in overcoming dysmenorrhea by doing abdominal stretching. Based on the initial anamnesis on 20 adolescent girls, it was found that 1 adolescent experienced severe dysmenorrhea, 4 adolescents experienced moderate dysmenorrhea, and the others only complained of mild discomfort during menstruation. From the results of evaluating teenagers' understanding of efforts to reduce dysmenorrhea, there was an increase of 33.55 points based on the average value. Through this socialization, it is expected to empower adolescents to make preventive efforts to overcome dysmenorrhea as a characteristic of community independence.